2013
DOI: 10.1111/odi.12176
|View full text |Cite
|
Sign up to set email alerts
|

Human periodontal ligament cell sheets cultured on amniotic membrane substrate

Abstract: We conclude that AM may represent a suitable substrate for culturing PDL cells and that PDL cells cultured on AM show sheet formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 36 publications
(45 reference statements)
1
22
0
Order By: Relevance
“…Oral mucosal epithelial cell [78] Corneal epithelium [80] Not needed Amniotic membrane Oral mucosal epithelial cell [7], Corneal endothelial cell [8], Corneal epithelium [10] Conjunctival epithelial cell [9], Amniotic epithelial cell [81], Keratinocyte [82], PDL cell [83] Temperature Temperature-responsive Somatic cell (epithelial): Corneal epithelium [51], reduction below polymer (PIPAAm)-Keratinocyte [13], Corneal epithelial cell [14], Esophageal mucosa 32°C grafted cell culture vessel Oral mucosal epithelial cell [15], RPE cell [16], [52] Middle ear mucosal cell [17], Urothelial cell [18], Alveolar epithelial cell [19], Tracheal epithelial cell [20] Somatic cell (non-epithelial):…”
Section: Key Materials Cell Type (Pre-clinical Study) Target Tissue Stmentioning
confidence: 99%
“…Oral mucosal epithelial cell [78] Corneal epithelium [80] Not needed Amniotic membrane Oral mucosal epithelial cell [7], Corneal endothelial cell [8], Corneal epithelium [10] Conjunctival epithelial cell [9], Amniotic epithelial cell [81], Keratinocyte [82], PDL cell [83] Temperature Temperature-responsive Somatic cell (epithelial): Corneal epithelium [51], reduction below polymer (PIPAAm)-Keratinocyte [13], Corneal epithelial cell [14], Esophageal mucosa 32°C grafted cell culture vessel Oral mucosal epithelial cell [15], RPE cell [16], [52] Middle ear mucosal cell [17], Urothelial cell [18], Alveolar epithelial cell [19], Tracheal epithelial cell [20] Somatic cell (non-epithelial):…”
Section: Key Materials Cell Type (Pre-clinical Study) Target Tissue Stmentioning
confidence: 99%
“…More importantly, in addition to the ability to differentiate into osteoblast-like cells and adipocytes, PDLSCs can also specifically differentiate into periodontal cells, such as cementoblast-like cells and collagen forming cells in vitro, and they possess the capacity to generate a cementum/PDL-like structure when they were transplanted into nude mouse and preclinical periodontal defect models. [5][6][7][8][9][10][11][12] Conventional hydroxyapatite (Ca 10 (PO 4 ) 6 (OH) 2 , HA) bioceramics had been used in periodontal bone tissue repair for their chemical similarity to bone mineral and their excellent biological activity and osteoconductivity. 13 However, it is reported that HA bioceramics lack osteoinductive ability, and consequently possess limited ability to form an interface with new bone tissue and hence hamper the new bone formation.…”
Section: Introductionmentioning
confidence: 99%
“…This was evident as the filaments on the basement side were more compact than those on the stromal side of the HAM. Adachi et al (2014) demonstrated that the stromal surface showed a hemi-desmosomal attachment between the cellmembrane interface, while only physical interlocking was seen on the basement membrane side of the HAM, as evident from both the transverse electron microscopy and immunohistochemistry.…”
Section: Discussionmentioning
confidence: 85%
“…Over the past few decades, with advancements in tissue engineering, biomaterial science and scaffold design, this 'miracle' membrane has been introduced into periodontal tissue engineering (Litwiniuk & Grzela 2014). Adachi et al (2014) demonstrated that periodontal cells cultured on amniotic membrane substrates express essential proteins for cell-substrate adhesion and the maintenance of tissue integrity. The HAM has also been shown to have good adhesion with periosteal-derived cell sheets and dental pulp-derived cell sheets Honjo et al 2014).…”
Section: Introductionmentioning
confidence: 99%